Otolith chemical composition as a useful tool for sciaenid stock discrimination in the south-western Atlantic - Volpedo, Alejandra (2006)
Striped weakfish (Cynoscion guatucupa) and whitemouth croaker (Micropogonias furnieri) are important commercial and recreational species found in abundance along the South American Atlantic coast. In recent years otolith chemical composition has been used as a tool for identifying fish stocks for several species. The chemical composition of C. guatucupa and M. furnieri otoliths was determined by inductively coupled plasma-optical emission spectrometry (ICP-OES) in samples from coastal sites (Partido de La Costa, Mar del Plata and San Blás Bay). Significant differences in the ratios of Mg/Ca, Mn/Ca and Sr/Ca for C. guatucupa otoliths and Cd/Ca, Cu/Ca, Mg/Ca, Sr/Ca and Zn/Ca for M. furnieri otoliths suggest the existence of two different fish stocks, one originating in the north (including Samborombón Bay and Partido de La Costa fisheries) and another originating in the south (including "El Rincón" and San Blás fisheries). These results agree with previous studies on the same species using different methodologies. These stocks may be separated by an oceanographic barrier, the "Frente El Rincón". Otolith chemical composition has not been previously used in South America for identifying fish stocks and may be a simple, quick and useful tool for the sustainable exploitation and management of commercial species.